Single-molecule manipulation of copper nanoclusters for modulating nonlinear optics - Xuekun Gong; Zhuang-Hua Liu; Qinghua Xu; Lin Wang; Qingxiang Guo; Jian Zhang; Qiao-Hong Li; Wei-Hui Fang; Hui Shen (Polyoxometalates)
The detailed elucidation of structure–property relationships at the molecular level in metal nanoclusters is highly valuable for advancing structure design and optimizing performance. However, effectively manipulating metal nanoclusters’ physical and chemical properties at the single-molecule level remains a significant challenge. Here, we demonstrate that single-molecule chemistry can effectively control the third-order nonlinear optical (NLO) performance of structurally precise copper nanoclusters. We present two analogous clusters, [Cu25(RS)18H10]3− (Cu25) and [Cu26(RS)18H10(PPh3)]2− (Cu26, where RSH is 2-fluorobenzenethiol), whose structures were determined in this study. Both clusters feature a Cu13 core in a centered cuboctahedron configuration with similar shell structures. However, Cu26 includes an additional PPh3Cu+ unit. This single structural difference significantly changes their properties, including optical characteristics and stability. Compared to Cu25, Cu26 exhibits enhanced optical limiting (OL) activity. Theoretical calculations indicate that the substantial electron transfer from the PPh3 ligand to the metal core enhances the NLO performance of Cu26. This study highlights the potential of structurally precise copper nanoclusters as OL materials and advances the understanding of nanoparticulate material fabrication using a single-molecule strategy.